On linearization of quadratic stochastic operators - Ganikhodjaev, Nasir; Usmanova, Maksuma; Anorov, Obidjon (2009)

(untitled)
Quadratic stochastic operators frequently arise in many models of mathematical genetics, namely theory of heredity. In this paper we study the linearization of quadratic stochastic operators, state some properties of the its Jacobian and consider some application of quadratic stochastic operators in medicine.